Islet xenotransplantation: what is the optimal age of the islet‐source pig?. (11th August 2014) - Nagaraju, Santosh; Bottino, Rita; Wijkstrom, Martin; Trucco, Massimo; Cooper, David K. C.
Abstract Background The need for pig islet xenotransplantation in patients with type 1 diabetes is compelling; however, the ideal age at which islets should be isolated from the donor pig remains uncertain. Pig islet transplantation in primates, as a valuable pre‐clinical model, has been explored using adult, neonatal, fetal pig islets, and also pancreatic primordia from pig embryos as beta cell donors. Neonatal pig islets have some advantages over adult and fetal islets, but the optimal age within the first month of life at which neonatal islets should be isolated and transplanted is as yet unclear. Methods In an attempt to answer this question, we carried out a literature search, but limited the search primarily to evidence in the clinically‐relevant pig‐to‐non‐human primate model. Results We identified surprisingly few studies in this model directed to this topic. Even in pig‐to‐rodent models, there were few definitive data. Conclusion From the few data available to us, we conclude that pancreatectomy and islet isolation from neonatal pigs may have advantages over adult pigs and that isolation during the first week of life may have minor advantages over later weeks.